The Use of Habitat Models in Conservation of Rare and Endangered Leafhopper Species (Hemiptera, Auchenorrhyncha) - Strauss, Barbara; Biedermann, Robert (Journal of insect conservation, 2005)
For conservation of Auchenorrhyncha species, knowledge of their habitat requirements is essential. However, for most species there is no 'quantitative' knowledge that would allow e.g. spatially explicit predictions. Such predictions can be made by habitat models, which quantify the relationship between the environment and the occurrence of species. In two plot-based case studies - the endangered leafhopper Verdanus bensoni in mountainous grasslands and four endangered Auchenorrhyncha in urban brownfields - we used habitat models to quantify the habitat requirements of these five species and to exemplify their use for creating habitat suitability maps. In the first case study, the multivariate model showed that occurrence probabilities of the leafhopper V. bensoni increase with both decreasing nitrogen indicator values and decreasing tree cover. On urban brownfields, successional age was a driving factor for species' occurrence. Site age largely determines a range of vegetation characteristics, which, in multivariate models, often replaced the variable age. Internal validation showed the robustness of all models. The models allow predictions of habitat quality under different management regimes (e.g. response to fertilization or abandonment for V. bensoni or to different turnover rates on brownfield sites). We discuss the application of habitat models in the conservation of Auchenorrhyncha, especially the use of habitat suitability maps.[PUBLICATION ABSTRACT]